Prevalence and distribution of intestinal parasitic infections in taeniasis endemic area of North Sumatera, Indonesia - Yulfi, Hemma; Darlan, Dewi M.; Panggabean, Merina; Andriyani, Yunilda; Rozi, Muhammad F.; Wandra, Toni (Narra Sains Indonesia, 2024)
A group of helminthic and intestinal protozoa causes intestinal parasitic infections (IPIs), affecting more than 2.5 billion people worldwide. IPIs are diseases closely associated with poor hygiene and sanitation, concentrated in underdeveloped regions and among populations with low socioeconomic status. Consequently, most prevalence is in Sub-Saharan Africa and Asia, with local habits or risk factors that could affect its prevalence. The aim of this study was to determine how hygienic practices, sanitation, and local behavior of eating raw meat (hinasumba) contributed to the prevalence of IPI. A cross-sectional study was conducted in the Simalungun District of North Sumatera Province, involving 428 people of Batak Simalungun. There were 15 villages randomly selected across the district based on the local registry, which consequently, non-purposive sampling was conducted. Face-to-face interviews assessed various risk factors, such as demographic characteristics, water source, traditional raw meat consumption, or hinasumba as local risk factors, hygienic practices, and sanitation. The findings indicated that an overall prevalence rate of IPI was 42.9%, consisting of 87.5% with helminthic infection and 12.5% with protozoal infection. More than half of IPI cases were associated with Taenia sp. infections (21.8%), followed by hookworms’ infections with a 6.1% positivity rate. Based on multivariate analysis, farming and consuming traditional delicacies, namely hinasumba, increased the likelihood of IPI occurrence among the population by 1.7 and 3 times, respectively. It can be concluded that the high prevalence of taeniasis in the study area was associated with local behavior and hinasumba consumption, which may contribute to determining the dominance of specific IPI species.